UMKM KEBUDAYAAN DI KABUPATEN MERANGIN, PROVINSI JAMBI: PELUANG, TANTANGAN, DAN STRATEGI PENGEMBANGAN - Riri Wulandari; Gion Ramahdan; Grafika Hijrah Kiska; Irwansyah; Popi Adella (Hira Institute, 2024)
Culture-based Micro, Small and Medium Enterprises (MSMEs) have great potential to improve the regional economy while preserving cultural heritage. Merangin Regency in Jambi Province has a rich traditional culture, including arts, crafts, cuisine, and tourist attractions. This article thoroughly examines the potential of cultural MSMEs in the Merangin Regency, highlighting the existing opportunities, the challenges faced, and further growth strategies. This research uses a qualitative approach by utilizing literature reviews, interviews with MSME stakeholders, and government policy analysis. The findings show that the development of cultural MSMEs requires collaborative support from the government, society, and the private sector and the adoption of digital technology to expand market access.